Interaction devices for multi-sensory exploration in immersive environments - Donga, João (2024)
Immersive environments, such as virtual reality (VR) and augmented reality (AR), provide users with experiences that blend digital and physical worlds. Interaction devices play a critical role in facilitating these experiences by engaging multiple human senses—sight, sound, touch, smell, taste and vestibular. This paper explores the various interaction devices designed for multi-sensory exploration, their applications, and the challenges associated with creating a fully immersive multi-sensory experience. We analyze input and output devices, hybrid systems, and emerging technologies while addressing the challenges in synchronization, user comfort, and accessibility.